Students as Partners in the Real World – A Whole-Institution Approach - Shaw, Natasha; Rueckert, Caroline; Smith, Judith; Tredinnick, Jennifer; Lee, Maddison (International Journal for Students as Partners, 2017)
Students as Partners (SaP) is an approach to student engagement that has gained much traction in recent years. Evidence shows that it adds value to the learning experience and provides opportunities for students to develop the capabilities needed in their future pathways. This paper documents one university’s approach to embedding partnerships in its institutional culture. The paper begins by contextualising the process in relation to wider institutional goals and outlines the three phases of implementation. This case study argues that to enable a whole-institution approach to SaP, it has been necessary to invest in strategies at a number of levels that enable partnership, from high-end policy and protocols to providing opportunities for staff and students to shape their own partnerships.